2011
DOI: 10.5897/ajmr10.866
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Vernonia amygdalina on selected urinary tract pathogens

Abstract: The aqueous ethanol and acetone-ethanolic extracts of Vernonia amygdalina leaves and stems were investigated for their antimicrobial activities compared to ciprofloxacin, against Escherichia coli, Klebsiella sp and Staphylococcus sp. The antimicrobial activity of each extract on the isolates was determined by agar well diffusion and minimum inhibitory concentration methods. The acetoneethanolic extract of the leaf showed the highest antibacterial activity on Klebsiella sp in both methods used, followed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
3
6
2
Order By: Relevance
“…Stem and leaf extracts of V. amygdalina have also been reported for antimicrobial role against Klebisella spp. (Uzoigwe & Agwa, 2011). The same authors have also shown that E. coli is not susceptible to extracts of V. amygdalina, which matches our own finding.…”
Section: Discussionsupporting
confidence: 90%
“…Stem and leaf extracts of V. amygdalina have also been reported for antimicrobial role against Klebisella spp. (Uzoigwe & Agwa, 2011). The same authors have also shown that E. coli is not susceptible to extracts of V. amygdalina, which matches our own finding.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been demonstrated that the acetone-ethanol extract of the leaves from V. amygdalina was weakly active against K . pneumoniae, E. coli, S. aureus , B. cereus, S. dysentriae and S. typhimurium [35] with MIC values ranged from 7.5 mg/mL to 25 mg/mL [42]. These activities are in accordance with the results obtained in the present work, but we observed higher antibacterial activity of this plant on all 29 bacteria including MDR phenotypes (with MIC values ranging between 256 and 1024 μg/mL).…”
Section: Discussionsupporting
confidence: 92%
“…The aqueous extracts of the plant samples were less active on the test organisms compared to the raw and alcohol extracts. This agrees with previous reports 12,25 that aqueous extracts of G. latifolium showed no activity against S. aureus and E. coli even at high concentrations. It was observed that in both forms of extraction i.e.…”
Section: Phytochemical Analysissupporting
confidence: 94%